EKSPLORASI DAN IDENTIFIKASI JAMUR ENTOMOPATOGEN PADA TANAMAN HORTIKULTURA DI DESA BOENTUKA, KECAMATAN BATU PUTIH, TIMOR TENGAH SELATAN - Killa, Yonce Melyanus; Dai, Yohana Petronela; Simamora, Agnes V.; Kleden, Yasinta L. (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Entomopathogen fungi are fungi that become pathogens in insects. This fungus lives, grows, and develops by taking nutrients from the host it is infected with so that the host is disrupted in its metabolism and will then die. This research aims to identify entomopathogen fungi from horticultural plants in Boentuka Village, Batu Putih District, South Central Timor. This research has been carried out from July to October 2022. Sampling of dead insects or infected with entomopathogenic fungi and soil was carried out in Boentuka Village while isolation and identification of entomopathogen fungi were carried out in the Microbiology laboratory, Faculty of Agriculture, Universitas Nusa Cendana. This research uses a purposive sampling method by taking samples based on observations of insects infected with entomopathogen fungi, which are then stored in sample bottles. In addition, soil samples from the site of the entomopathogen fungi attack were also taken and taken to the laboratory, with Tenebrio molitor larvae being used as bait to catch the entomopathogen fungi. The fungi that grew on the larvae and samples of the insects was then isolated and identified. The parameters of observation are the characteristics of isolates that grow macroscopically and microscopicly. The results of the research obtained four isolates of entomopathogen fungi Aspergillus flavus, Aspergillus niger, Beauvaria bassiana, and Fusarium sp. In the future, this isolate will be tested for its ability as a biological agent for pest control in vitro and in vivo.